Philosophy of the city: to the problem of humanity of urban space - Novikava, Volha U. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The subject of socio-philosophical research in the article is the phenomenon of the city. Various types of cities are considered from the point of view of their continuity: an open antique city, a closed medieval city, a contemporary multicultural city. Attention is paid to the influence of the city on the processes of human self-identification, the relationship of the city with the mentality and physicality of a person. The features of the organisation of urban space are analysed, its human dimension is revealed. Human dimension of the cite manifests itself in the mutual similarity of a person and a city, which evolves both spontaneously and purposefully. The phenomenon of public space is considered. The article examines the «time of cities», the experience of which, historically determined by class differences, in the modern world is closely related to the specifics of urban space. Particular attention is paid to the phenomenon of the city dweller: from the citizen of the ancient polis to the contemporary reminiscence of the flaneur.
Keywords: city; person; identity; urban space; time of cities; public space; flaneur